"Lost to Follow-up" Among Adult Cancer Survivors. (October 2018) - Gill, Amitoj; Gosain, Rohit; Bhandari, Shruti; Gosain, Rahul; Gill, Gurkirat; Abraham, Joseph; Miller, Kenneth
Abstract : Background: Follow-up cancer care is important for patients who have received IV chemotherapy but some patients discontinue their care and are lost to follow-up (LFU) at the cancer center where they were treated. The purpose of this study was to determine what proportion of cancer survivors are LFU at 5 years after treatment, the timing of LFU, and the characteristics of those who do not continue survivorship care. Methods: Adult patients with cancer who were treated with chemotherapy at a large community teaching hospital in 2006 and 2007 were identified and linked with State tumor registry data. Hospital medical records were reviewed to obtain information on demographics, diagnosis, treatment, and date of last follow-up visit. Characteristics of patients with ≥5 years of follow-up care were compared with those who were LFU. Results: In total, 487 patients received chemotherapy and 304 died (62%) during the 5-year follow-up period. Among the 183 cancer patients who were known to be alive at 5 years, 92 (50%) were LFU and 50% (46/92) of this LFU group were LFU within 1 year of diagnosis. At 5 years, follow-up care was continuing for 55% of women, compared with 39% of men. The highest proportion of follow-up was observed among lung cancer patients (84%), followed by patients with breast cancers (63%) and gastrointestinal cancers (40%). Patients with hematological cancers had the lowest follow-up proportion at 5 years (29%) ( P <0.05). Follow-up was not significantly associated with age ( P =0.48), insurance status( P =0.29), and race( P =0.06). Conclusions: It is estimated that 65% of the cancer survivors in the United States are ≥5 years beyond their diagnosis but there is little data on oncology follow-up rates. In our retrospective study of 183 patients who were treated with chemotherapy only 49.7% continue to follow-up at their treatment center. LFU has important implications in planning long-term care strategies for cancer survivors and in survivorship research.